Cytologic Analysis of a Glomus Tumor in the Left Second Toe: Case Report. (28th October 2021) - Hwang, J; McDowell, S; Cole, B; Huber, A R; Reyes, C
Abstract: Introduction/Objective: Glomus bodies reside in the stratum reticularis of the dermis as well as in visceral organs. Their functions involve temperature and blood pressure regulation. The incidence of glomus tumors is approximately 1.5%, occur more frequently in women, and generally manifest during the third to fifth decade of life. A majority of glomus tumors are diagnosed by biopsy and excision. At least 19 case reports exist in the literature where glomus tumors are diagnosed by fine-needle aspiration (FNA). We add to this growing literature by discussing a case report involving the cytologic findings of an FNA-diagnosed glomus tumor. Methods/Case Report: A 66-year-old female presented with left second toe pain for 41 years but worsening in the past several months. Physical exam revealed 5/5 muscle strength in her toes without loss of sensation. There was no edema, erythema, nor ecchymosis. Pain was notably out of proportion when palpating her second nailbed. Magnetic resonance imaging (MRI) with contrast was performed revealing a 1.1 x 1.0 x 0.9 cm circumscribed, ovoid mass involving the dorsal aspect of the second toe distal phalanx along its dorsal margin (Figure 1). The patient underwent fine needle aspiration and biopsy. Cytologic findings included clusters of uniform cells with round to oval nuclei and scant cytoplasm. There was spindling of cells noted in some of the clusters. Cells were surrounded by thick wisps of magenta colored myxoid material reminiscent of a pleomorphic adenoma (Figure 2). Biopsy showed uniform cells surrounding capillaries. Immunohistochemistry performed on the biopsy showed that lesional cells were positive for alpha-smooth muscle actin (SMA). A diagnosis of glomus tumor was made. Amputation was performed with clear margins. Results (if a Case Study enter NA): NA Conclusion: Glomus tumor is a rare tumor that is usually diagnosed on biopsy; however, it has distinct cytologic features that can aid in its diagnosis on fine needle aspirations.